Reducing blood loss in revision total hip and knee arthroplasty: tranexamic acid Is effective in aseptic revisions and in second-stage reimplantations for periprosthetic infection - Reichel, Franz; Peter, Christoph; Ewerbeck, Volker (BioMed research international, 2018)
Introduction. The aim of the study was to determine the usefulness of tranexamic acid (TXA) in revision total hip arthroplasty (rTHA) and revision total knee arthroplasty (rTKA). We analyzed the perioperative blood loss with and without TXA in aseptic rTHA and rTKA as well as in second-stage reimplantation for hip and knee periprosthetic infection. Materials and Methods. In this prospective cohort study, 147 patients receiving TXA (96 rTHA, 51 rTKA) were compared to a retrospective cohort of 155 patients without TXA (103 rTHA, 52 rTKA). The TXA regimen consisted of a preoperative bolus of 10 mg/kg bodyweight (BW) TXA plus 1 mg/kgBW/h perioperatively. Given blood products were documented and the perioperative blood loss was calculated. Thromboembolic events were registered until three months postoperatively. In subgroups, the effects of TXA were separately analyzed in 215 aseptic revisions as well as in 87 reimplantations in two-stage revisions for periprosthetic infection. Results. Both TXA groups showed a significantly reduced mean blood loss compared to the respective control groups. The TXA group of rTHA patients had a mean blood loss of 2916 ml ± 1226 ml versus 3611 ml ± 1474 ml in the control group (p<.001). For the TXA group of rTKA patients, mean calculated blood loss was 2756 ml ± 975 ml compared to 3441 ml ± 1100 ml in the control group (p=.0012). A significantly reduced blood loss was also found in the TXA subgroups for aseptic and septic revision procedures. No thromboembolic events were recorded among the TXA groups. Conclusions. There is a significant reduction of perioperative blood loss under TXA influence without an increased incidence of adverse events. The standard use of TXA can be recommended in aseptic hip and knee revision arthroplasties as well as in second-stage reimplantations for periprosthetic infection.
Gesehen am 28.11.2018